Synthesis of a Polymer Covering on Al(OH) and BaSO Surfaces by Means of Radical Polymerization in Water Medium - V. Tokarev; V. Seredyuk; S. Voronov (Adsorption Science & Technology)
The graft polymerization of butyl methacrylate on to the surface of Al(OH) 3 and BaSO 4 fillers initiated by an adsorbed peroxidic macroinitiator was studied in water medium relative to the corresponding polymerization in toluene. It was established that, in water medium, the nature of the solid surface as well as the monomer concentration has only a very slight influence on the rate of grafting and the amount of polymer grafted, both of which depend on the specific surface area of the filler and the temperature. To explain these features, a microreactor polymerization model is proposed in which the filler particles or aggregates of the particles together with the immobilized macroinitiator and adsorbed monomer are considered as microreactors. As a result of graft polymerization, compatibilizing polymer shells were formed on the Al(OH) 3 and BaSO 4 particles. Due to solvation, such shells enhance the organophilicity of the filler surface sufficiently and provide a high steric stabilization of the filler dispersions in organic media. When both the adsorption of the macroinitiator and the graft polymerization of the monomer proceed in water medium, the efficiency of the process and its ecological cleanliness are increased greatly.